Evaluasi Efikasi Diri dan Persepsi Kredibilitas Pengguna Sistem Informasi Perencanaan dan Penganggaran pada Badan Perencanaan, Penelitian, Pengembangan Kota Malang dengan Metode Technology Acceptance Model (TAM) Termodifikasi - Handhika Baskoro Dwi Hatmojo; Yusi Tyroni Mursityo; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Sistem Informasi Perencanaan dan Penganggaran is an application that used to help process preparation Regional Government Work Plan in Malang City. The ability of employees in the Regional Work Unit to use computer is uneven, that consequence to the use of the Sistem Informasi Perencanaan dan Penganggaran doesn't runnning as expected. Some functionalities found often problematic make users perception of credibility towards the Sistem Informasi Perencanaan dan Penganggaran is decreased and were questioned. The research conducted using the modified Technology Acceptance Model (TAM) method with aiming to describe user acceptance of variables perceived usefulness, perceived ease of use, computer self-efficacy, perceived credibility and behavioral intention. The type of this research is a quantitative research with data collection techniques is using questionnaires with a population is all users of Sistem Informasi Perencanaan dan Penganggaran. The sampling technique used is a total sampling technique with data analysis process using statistic descriptive technique. The result showed that variables perceived usefulness and behavioral intention is belong to the very high category, variables perceived ease of use and perceived credibility belong to the high category, and variabel of computer self-efficacy belong to the medium category. Recommendation given to each indicators that has a value below the average.